Different characteristics of tuberculous pleural effusion according to pleural fluid cellular predominance and loculation - Lee, Jaehee; Lim, Jae Kwang; Yoo, Seung Soo; Lee, Shin Yup; Cha, Seung Ick; Park, Jae Yong; Kim, Chang Ho (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Tuberculous pleural effusion (TPE) exhibits different characteristics according to pleural fluid cellular predominance or whether the pleural fluid is free-flowing or loculated. However, its categorization based on either of these factors alone may be insufficient to properly reflect the heterogeneous manifestation of TPE. We evaluated the characteristics of the four TPE groups classified according to cellular predominance and whether the fluid is free-flowing or loculated. Methods: A cohort of 375 patients with TPE was retrospectively reviewed. Clinical, radiological, and laboratory findings were compared between neutrophilic and lymphocytic TPE, and between free-flowing and loculated effusion for both neutrophilic and lymphocytic TPE. Results: Lymphocytic TPE and neutrophilic TPE were observed in 336 (90%) and 39 (10%) patients, respectively. Pleural fluid loculation was present in 36% and 31% of the patients in the lymphocytic and neutrophilic groups, respectively. A few parameters of the laboratory findings between neutrophilic and lymphocytic TPE patients showed significant differences. However, these significant differences were prominently observed when comparing free-flowing and loculated subgroups of the respective neutrophilic and lymphocytic groups. Pleural fluid pH, lactate dehydrogenase, and adenosine deaminase levels were significantly different among the four subgroups. The neutrophilic loculated subgroup exhibited the most intense pleural inflammation and the highest mycobacterial yields when compared to the other subgroups. However, the percentage of neutrophils in the pleural fluid was not positively associated with the probability of culture-positive effusion. Conclusions: The heterogeneous manifestation of TPE would be better characterized by using a classification system based on combined pleural fluid cellular predominance and loculation, with the neutrophilic loculated subgroup contributing to most of the clinically significant differences.